Hazard Identification, Risk Analysis, and Risk Control Management in Coffee Farmer in Pekon Trimulyo, Gedung Surian Subdistrict, West Lampung Regency: Sulistiarini, Bougenvil Ungu, Faizal, Fitroh Cahyaningtyas, Ghina Gabrilla Yusuf, Nur Aina Suri, Sindi Diniati, Fitria Saftarina - SULISTIARINI; BOUGENVIL UNGU; FAIZAL; FITROH CAHYANINGTYAS; GHINA GABRILLA YUSUF; NUR AINA SURI; SINDI DINIATI; FITRIA SAFTARINA (Jurnal Agromedicine Unila: Jurnal Kesehatan dan Agromedicine, 2026)
Coffee cultivation is one of the agricultural sectors that significantly contributes to the economy of communities in Lampung Province, Indonesia. However, various activities involved in the cultivation process may pose occupational hazards that can affect farmers’ health and safety. This study aimed to identify hazards, assess risk levels, and formulate risk control measures in coffee cultivation activities in Pekon Trimulyo, Gedung Surian District, West Lampung Regency. The study employed a descriptive observational design using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) approach. Data were collected from March 25–30, 2026, through direct observation, interviews, and documentation involving a coffee farmer selected through purposive sampling based on participation in all stages of coffee cultivation. Risk assessment was conducted using a 4×4 risk matrix based on the likelihood of occurrence and severity of consequences, while risk control recommendations were developed according to the Hierarchy of Controls principles. The results showed that potential hazards were present throughout all stages of coffee cultivation, including nursery management, land preparation, fertilization, crop maintenance, harvesting, and post-harvest activities. Identified hazards consisted of physical, chemical, biological, ergonomic, and mechanical hazards. Most risks were categorized as moderate and were associated with exposure to environmental heat, slippery land conditions, manual material handling, and non-ergonomic working postures. High-risk activities were identified in pest and weed control operations due to the use of insecticides and herbicides, which may cause both acute and chronic health effects. Risk control measures were recommended through hazard elimination, substitution of high-risk substances, engineering controls, administrative controls, and consistent use of personal protective equipment (PPE). The implementation of a hierarchical control approach is expected to improve farmers’ occupational safety, reduce the risk of work-related illnesses, and support the sustainability of coffee farming productivity. Keyword: hazard Identification, risks analysis, HIRARC, Coffee agriculture.